Pengaturan Perbatasan Di Laut Mediternia Antara Turki Dan Yunani Dalam United Convention Los 1982 - June Mitchen Rumlaklak; Johanis Steny Franco Peilouw; Josina Augustina Yvonne Wattimena (TATOHI: Jurnal Ilmu Hukum, 2022)
Introductioan: The 1982 Convention on the Law of the Sea is the first and most comprehensive and comprehensive convention relating to the territorial sovereignty of a country over the use and use of marine natural resources.Purposes of the Research: This study aims to find out and understand about the border arrangements in the Mediterranean Sea between Turkey and Greece in Unclos 1982.Methods of the Research: The research method in this study is a normative legal research, using a law approach and a conceptual approach. Sources of research data include primary, secondary, tertiary legal sources. Data collection techniques in the form of literature study. Processing and analysis of legal materials used in writing is using qualitative analysis method.Results of the Research: The results obtained are that maritime border arrangements are very important in cases of maritime border territorial disputes between Turkey and Greece according to international law, maritime boundaries are also a guarantee in the process of resolving cases between the two countries. This is expressly stipulated and regulated in the provisions of international law as international law regulates the state to have the authority to resolve and enforce maritime border disputes in the territory of the countries of Turkey and Greece. As well as the process of resolving conflicts over maritime border area disputes in Turkey and Greece, it is clear that there must be a settlement because this is the main factor to prevent maritime border territorial disputes from occurring, therefore it is necessary to take relative measures to resolve them in accordance with the provisions of the law. Applicable provision.